Analisis Faktor Yang Meningkatkan Keaktifan Belajar Siswa Dalam Memotivasi Kegiatan Belajar - Sudrajat, Husaen; Alfan Hadi (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
The purpose of this study is to see and understand what factors can increase student learning activity to increase student motivation in the teaching and learning process. This research is qualitative descriptive research, which is intended to describe everything related to learning activities in the classroom and factors that can increase students' activeness and learning so that they are more motivated to follow the teaching and learning process. This research was conducted in grade 5 of SDN 3 Nyerot. This study uses data collection techniques from observation, interviews and documentation. Data analysis is inductive analytical. The results of the study show that the factors that can increase students' learning activity in the learning process consist of internal factors, namely physiological and psychological factors. Psychological factors include attention, responses, memories, motivation. Meanwhile, external factors are the social environment (teachers, classmates), non-social environments (facilities and infrastructure) and learning approach factors, namely varied learning methods and diverse learning media.